An experimental study on energy-exergy analysis and sustainability index in a diesel engine with direct injection diesel-biodiesel-butanol fuel blends. (15th May 2020) - Sarıkoç, Selçuk; Örs, İlker; Ünalan, Sebahattin
Graphical abstract: Highlights: The effect of the biodiesel-butanol properties on energy-exergy analyses and SI. The highest energy-exergy and SI values of the engine obtained for B100 at 1400 rpm. Butanol rate has exhibited considerably effects on energy-exergy and SI values. Oxygen content, CN, vaporization properties have affected the energy-exergy and SI. D75B20But5 blend can be considered the best fuel in terms of the energy-exergy and SI. D75B20But5 blend may be used instead of euro diesel without any major modification. Abstract: The aim of this study was to investigate the effects of biodiesel and butanol properties on energetic-exergetic efficiencies of the engine performance and assessment of sustainability. In this study, energy and exergy analyses were performed in a direct-injected (DI) diesel engine operating with various diesel-biodiesel-butanol fuel blends. The experiments were conducted with a single-cylinder, naturally aspirated, water-cooled, a DI diesel engine at the maximum torque (1400 rpm) and power (2800 rpm) condition. According to obtained results, it was found that biodiesel energetic-exergetic efficiencies and sustainability index (SI) of biodiesel were higher than euro diesel. The maximum energy-exergy efficiencies and SI of the diesel engine were 32.49%, 30.25%, and 1.434, respectively and were obtained using B100 fuel at 1400 rpm. However, low butanol ratio blends had considerably similar energetic-exergetic performance and SI trends compared to euro diesel, while these values decreased by increasing the butanol ratio. Thus, D75B20But5 can be accepted as fuel that has the best fuel ratio according to the performance of the energy-exergy and SI. It could be concluded that the properties of the biodiesel and butanol have substantially affected the energy-exergy analysis and SI value of a direct-injected diesel engine.